Contribuição ao conhecimento químico de produtos naturais do litoral cearense: Esponja Aplysina fulva e actinomicetos (Streptomyces sp. e Micromonospora sp.) - Cesário, Hozana Patrícia Silva de Freitas (2023)
The chemical investigation from the extract of Aplysina fulva sponge and three marine bacteria of the genera Streptomyces sp. and Micromonospora sp are described. The research aimed to isolate and characterize secondary metabolites and investigate their biological activities. For the fractionation and isolation of the compounds, chromatographic techniques such as liquid-liquid partition, Sephadex LH-20, and high-performance liquid chromatography (HPLC) were used. The structural determination of the compounds was performed by analysis of spectroscopic techniques (1H and 13C NMR and MS). The chemical investigation of A fulva resulted in the isolation of nine compounds: (3,5-dibromo-4-hydroxyphefyl)-N,N,N-trimethylethanammonium (1), (3,5-dibromo-4-methoxyphefyl)-N,N,N,trimethylethanammonium (2), cis-(3,5-dibromo-4-ethoxy-1-hydroxy-4-methoxycyclohexa-2,5-dien-1-yl] acetic acid (3), 3,5-dibromo-1-hydroxy-4-oxo-2,5-cyclohexadiene-1-acetamide (4), (3,5-dibromo-4-hydroxyphenyl)-acetamide (5), 7-[3,5-dibromo-4-[(13-oxo-10-oxazolidinyl)]-methoxyphenyl]-1-oxazolidinone] (6), (13-oxo-12-hydroxy-homoaerothionine (7), fistularin-1 (8) and fistularin-3 (9), all previously isolated in the genus. The main compounds (4, 6, and 9) were subjected to the anxiety test on zebrafish (Danio rerio), showing an anxiolytic effect via the GABAergic system, which was compatible with in silico Molecular Docking studies. The investigation of the crude EtOAc extract, produced by a bacteria strain of the genus Streptomyces sp., resulted in the isolation of the compound dithioloformamide, whose anxiolytic activity was also evaluated on zebrafish, exhibiting an anxiolytic effect via the serotonergic system, according to Molecular Docking and Dynamics studies. The EtOAc extract, produced by a Streptomyces sp. strain recovered from sediment collected on Paracuru beach-CE beach, resulted in the isolation of four chromomycins: A2 (10), A3 (11), demethylchromomycin A2 (12), and pre-chromomycin A2 (13), among which chromomycin A2 exhibited potent anticancer activity against metastatic melanoma cancer cell lines. The chemical reinvestigation of the hexane and AcOEt extracts from a Micromonospora sp. strain led to the isolation of nine polycyclic quinones, of which six had already been previously isolated. The compounds 12-hydroxy-9-propyltetracene-6,1-dione (14), 4-methoxy-9-propyltetracene-5,12-dione (15), and 4,6-dihydroxy-3-methoxycarbonylmethyl-6a-(isobutyl)-5,12-anthraquinone (16) are being reported for the first time.